ANALISA SINKRONISASI ALAT GALI MUAT DAN ALAT ANGKUT TERHADAP REALISASI PRODUKSI OVERBURDEN DI PT DUTA ALAM SUMATERA - Kemas Moh. Ade Isnaeni; Anugrah Jodi Pratama; Muhammad Ali Malik (Bajang Institute, 2023)
The mining activities at PT Cahaya Riau Mandiri jobsite PT Duta Alam Sumatera applied conventional mining method, namely using the combination of loading and hauling equipment. The mining activity for overburden removal at PT Duta Alam Sumatera had equipment synchronization of MF >1 where the loading equipment had waiting time. To obtain the synchronized time, the reduction of hauling tools was necessary so that production activities especially overburden hauling could run optimally without any waiting time. The use of need equipment especially on the overburden activity utilized 5 units of DT Nissan CWB 45 and 1 unit of Komatsu PC 400 loading tool. Fleet 1 had production of 118.21 BCM/hours with match factor 1.46. Fleet 2 had production of 111.13 BCM/hours with match factor 1.52. Fleet 3 had production of 113.70 BCM/hours with match factor 1.46. The number of hauling tool could accelerate the mining activities without any waiting time from the almost close match factor